Mathematical Belief Profile of Seventh-Grade Students in Sleman Regency, Yogyakarta City - Ni Kadek Dianita (Universitas Negeri Semarang, 2022)
Abstract. Students’ mathematical belief is one of the factors that influence how students do mathematics. Teachers are expected to conduct a preliminary study before making a lesson plan so that learning can run meaningfully. This study aims to describe the profile of students’ mathematical beliefs of seventh graders in Sleman Regency based on high and low categories, as well as gender differences. This research is quantitative and descriptive. It was conducted in six junior high schools in Sleman Regency with 140 students. First, students filled out a Questionnaire about Students’ Mathematical Beliefs, then some students were interviewed for a deeper understanding of the topic. The findings of this study indicate that there is a tendency for overconfidence in male students with high mathematical belief levels, while female students are more careful. Then, male students with moderate levels showed hesitation in working independently. However, they are willing to do the work themselves. The indecision of female students depends on the material, if they like the material they will be more confident. Male students with low mathematical belief levels will try to avoid mathematics. Meanwhile, although female students are more willing to take mathematics lessons, they have a fixed mindset. Both genders felt that teachers favored the smarter students. Based on these findings, most students realize the importance of mathematics. Then, students’ self-confidence and the teacher’s role in learning are two things that affect students’ mathematics learning. Therefore, teachers are facilitators and motivators for students in mathematics learning so that they can assist students in enhancing students’ mathematical beliefs.